Pengembangan Kompetensi Sumber Daya Manusia Berkarakter Technopreneurship pada UMKM di Kelurahan Meruya Utara - Paijan, Paijan; Anah, Sri; Sugiharjo, R. Joko (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
In the current context of global market competition, it is crucial for human resources in micro, small, and medium enterprises (MSMEs) to be able to compete with large corporations that have already adopted digital technologies. MSMEs in North Meruya Village face several challenges, including limited production capabilities, suboptimal workforce performance, and inadequate mastery of digital technology. To address these issues, a community service program has been initiated. This program is conducted through face-to-face sessions, where a team of lecturers from Mercu Buana University, Management program, delivers training materials. The program aims to enhance the quality and competence of the MSME participants, broaden their knowledge and perspectives, and strengthen their ability to compete in both domestic and international markets. All of these goals are underpinned by the foundational values of entrepreneurship and technopreneurship that guide the teaching.